The answer to the given expression (-7) + b = (-11) is -4
<h3>How to solve an expression</h3><h3 />
(-7) + b = (-11) = -4
-7 + b = - 11
b = -11 + 7
b = -4
Learn more about evaluating expression:
brainly.com/question/4344214
Answer:
$50.4
Step-by-step explanation:
The Commission is $50.4 of the sale.
7% of 720 = 50.4
Answer:
175 (b)
Step-by-step explanation:
25*14=350
350/2=175
Answer:
Step-by-step explanation:
Using Pythagoras' identity in the right triangle
The square on the hypotenuse h is equal to the sum of the squares on the other 2 sides, that is
h² = 2² + 3² = 4 + 9 = 13 ( take square root of both sides )
h =